Female and male differences in AIDS diagnosis rates among people who inject drugs in large U.S. metro areas from 1993 to 2007. - West, Brooke S; Pouget, Enrique R; Tempalski, Barbara; Cooper, Hannah L F; Hall, H Irene; Hu, Xiaohong; Friedman, Samuel R (Annals of epidemiology, 2015)
We estimated female and male incident AIDS diagnosis rates (IARs) among people who inject drugs (PWID) in U.S. metropolitan statistical areas (MSAs) over time to assess whether declines in IARs varied by sex after combination antiretroviral therapy (cART) dissemination.